First report of anthracnose caused by Colletotrichum gloeosporioides on Brachychiton populneus in Argentina - Colombo, Denis Nahuel (2024)
Brachychiton populneus (brachychiton, kurrajong) is widely grown as a street tree in La Pampa, Argentina. During 2020, 95 urban trees were surveyed for foliar disease. Symptoms, not previously recorded, were detected on leaves of B populneus in the northern region of the province. These began as small, circular to irregular, brown, necrotic lesions on both sides of the leaf blade, turning black with a grey central area as they aged, arranged randomly on the leaf surface. Brachychiton populneus (brachychiton, kurrajong) se cultiva ampliamente como árbol de calle en La Pampa, Argentina. Durante 2020, se censaron 95 árboles urbanos para detectar enfermedades foliares. Se detectaron síntomas, no registrados previamente, en hojas de B populneus en la región norte de la provincia. Estos comenzaron como lesiones pequeñas, circulares a irregulares, marrones y necróticas en ambos lados de la lámina de la hoja, que se tornaron negras con un área central gris a medida que envejecían, dispuestas al azar en la superficie de la hoja